Adsorption of Heavy Metals Contaminants in Used Lubricating Oil Using Palm Kernel and Coconut Shells Activated Carbons - Opoku, Boadu Kwasi; Friday, Joel Ogbonna; Kofi, Essumang David (My University, 2020)
Abstract: This research work investigated the adsorption of some heavy metals contaminants in used lubricating oil using chemically activated carbon adsorbents produced from palm kernel and coconut shells. The adsorption mechanism was able to remove some heavy metals such as zinc, chromium, cadmium and magnesium contaminants from the used lubricating oil to appreciable levels. For instance, zinc from initial concentrations of 16.475±0.950 ppm before to 10.375±0.171 ppm after filtration processes for used lubricating oil sample A. Also, for coconut shell from an initial concentration of 14.575±0.272 ppm to 5.450±0.3000 ppm after filtration processes. It was observed that the coconut shell activated carbons was effective in the removal of lead metals while palm kernel cannot. However, the activated carbons produced from palm kernel and coconut shells are not suitable for the removal of both copper and iron metals. For example, after the filtration process with the palm kernel shell activated carbon, the mean concentration of copper metal increases for virgin (C) 0.001± 0.000 to 0.075±0.013 ppm and used lubricating oil samples (A&B) from 0.150±0.008 to 0.400±0.018 ppm and from 0.220±0.096 to 0.230±0.008 ppm respectively. Also, in the case of the coconut shell activated carbon, the mean concentration of copper in virgin lubricating oil remains the same 0.001±0.000 whereas for used lubricating oils samples (i.e. A&B) it increases from 0.150±0.008 to 0.780±0.014 and from 0.220±0.096 to 0.790±0.026 respectively. Also, the equilibrium adsorption data were analysed using the Langmuir isotherm model. The fit of this isotherm model to the equilibrium adsorption data was determined, using the linear coefficient of correlation (R2). The following R2 values were obtained; Copper (0.8185), Cadmium (0.8347), Lead (0.9349), Chromium (0.9378), Iron (0.9927), Zinc (0.9953), and Magnesium (0.9997) respectively. From the results obtained and statistics point of view, it can be concluded that the Langmuir model shows a better fit due to the high coefficient of correlation (R2 ≈ 1). The recovered oil could be also re-used.
Keywords: Activated Carbons; Heavy Metals; Contaminants; Used Lubricating Oils; Adsorption; Langmuir Isotherm Model; Correlation Co-efficient; Evbuomwan Benson Osa; Université de Ouaga; CFOREM; ACE: Training, Research and Expertise in Drug Sciences